Study of low power Laser effect on the healing of tibial fracture treated by intramedullary pin in rabbits - Omar, Raffal A.; Saleh, S. I. (The Iraqi Journal of Veterinary Medicine, 2003)
The effect of low power laser (LPL) on the healing of distal third of tibial fractures has been studied radiologically. Fractures induced in twenty-five local breed rabbits, immobilization achieved by using Steinman intramedullary pins, which was not removed during the period of study for 7 weeks. Irradiation with LPL was made by direct contact between the source and the site of fracture directly after the operation and then daily for fifteen days. Each fracture was studied radiologically after the first day from the operation until complete healing occurs. This study confirm that the healing of distal third of tibial fracture was very slow in control group and LPL accelerate the process of fracture healing in treated groups. With notice that the surface of fractured bone exposed to the source of laser therapy (medial side) was healed better than the non - exposed surface (lateral side). Finally there was no clear difference between treated groups.